Contemporary learning methods and the „new” roles of teaching practitioners - Kulpa-Puczyńska, Aleksandra (Forum pedagogiczne, 2024)
The article focuses on a modern approach to the learning process and the development of competencies. This does not only concern the Internet generation (Tapscott 2010), characterised by, among other things, the need for constant access to information and the pursuit of novelties – also in terms of innovative, engaging ways of acquiring knowledge. Taking the above into account, educators should ensure inclusivity and attractiveness of the educational environment, enabling the reconciliation of diverse student needs, by creating appropriate spaces such as: architectural, virtual, for individual and group work, sparking curiosity, and supporting the courage of learners when solving problems, not only educational ones. Through collaboration with other members of the school/university community, educators increasingly often create innovative environments for other practitioners, sharing experiences and teaching materials. Contemporary teachers are also expected to be attentive to social partners. On the other hand, the new generation of students values, for example: openness to learning in conditions of social interaction and the improvement of skills related to learning.